Nasal saddle deformity in rheumatological diseases: A review (Research, Society and Development, 2023)
Objective: Analyze the association of saddle nose deformity with rheumatologic diseases. Methods: This is a narrative literature review based on the guiding question: “What is the occurrence of saddle noses in patients with rheumatological diseases?” Data collection was carried out in the BVS, PubMed, and Scielo databases using the boolean operator “OR” and the following Medical Subject Headings (MeSH): Rheumatic diseases; Nose deformities acquired; Granulomatosis with polyangiitis; Relapsing polychondritis and ANCA-associated vasculitis. The selection of publications followed the following eligibility criteria: full articles available electronically, in Portuguese, English, or Spanish, published between 2015 and 2022, whose titles and abstracts are congruent with the purpose of the literature review. Works that differ from the research objective, as well as theses, dissertations, monographs and annal summaries were not selected. Results: Data collected were subjected to careful analysis resulting in a final sample of 22 scientific articles. The results obtained corroborate the association between the saddle nose and the immune-mediated diseases called granulomatosis with polyangiitis and relapsing polychondritis and allowed the recognition of new correlations between this nasal deformity and other rheumatological conditions, eosinophilic granulomatosis with polyangiitis, sarcoidosis, and IgG4-related disease. Conclusion: It is necessary to produce more scientific studies that evaluate the occurrence of saddle noses in rheumatic diseases to expand the evidence and scope of the subject and to elucidate the differential diagnoses associated with saddle noses.